Peanut seed tegument is affected by liming and drying method - Fernandez, E. M.; Rosolem, Ciro Antonio [UNESP]; Oliveira, DMT (Ista, 2000)
Calcium plays a fundamental role in cell division and growth, and is an important constituent of the cell wall. An increase in Ca concentration in the tegument of peanut (Arachis hypogea L.) seeds in response to lime application can affect its structure. The tegument structure can also be affected by the drying method of the seeds. The effects of lime application and drying methods as affecting the peanut seed tegument structure were studied in seeds from a field experiment conducted in Sao Manuel, São Paulo, Brazil. Peanut (cv. Botutatu, Valencia Type) was grown in presence or absence of 2.1 Mg ha(-1) of lime and dried in an oven, in shade and in the field. The tegument anatomical features were described and its structure was analysed. Pectic substances, lipidic reserves and starch accumulation were studied. The peanut tegument exhibited well differentiated exotesta, mesotesta and endotesta rich in pectates and covered by a cuticle. Tannin was not observed but there was lipid accumulation in mature teguments. Lignin was observed in the vascular bundles. Lime increased the tegument thickness and decreased the central cavity mainly in the exotesta cells when the period of seed drying was shortened. The effect of drying method upon the tegument was more noticeable in seeds grown without lime. It can be inferred that liming increased the resistance of the tegument.